A DISCOURSE ANALYSIS OF LEXICAL COHESION ON NAILA FARHANA’S VIDEOS - BATUBARA, WINDA WASALWA; HIDAYAT, DIDIN NURUDDIN; HUSNA, NIDA; ALEK, ALEK; MACHFUDI, MOCH. IMAM (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The study sought to investigate the lexical cohesion in three YouTube videos by Naila Farhana,